Halogen-free flame-retardant modified hydrocarbon resin, preparation method thereof, resin composition for copper-clad plate and application of resin composition
A halogen-free flame-retardant modified hydrocarbon resin with organic silicon side chains and benzocyclobutene groups addresses the deficiencies of existing hydrocarbon resins, providing improved flame retardancy, heat resistance, and dielectric properties for high-frequency printed circuit boards.
Patent Information
- Application Number
- CN202411086823.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2024-12-13
AI Technical Summary
Existing hydrocarbon resins used in copper-clad laminates suffer from poor flame retardancy, heat resistance, low glass transition temperature, insufficient rigidity, and large thermal expansion coefficient, which are inadequate for high-frequency and high-speed printed circuit boards requiring halogen-free flame retardancy, better dielectric properties, and dimensional stability.
A halogen-free flame-retardant modified hydrocarbon resin is developed, comprising a hydrocarbon resin main chain with organic silicon side chains and benzocyclobutene groups, prepared through hydrosilylation, Heck reaction, and hydrogenation, enhancing flame retardancy, heat resistance, and dielectric properties.
The modified resin achieves halogen-free flame retardancy, improved heat resistance, and excellent dielectric properties, with the resin composition for copper-clad laminates reaching UL94 V0 level and exhibiting a dielectric constant of 2.53 to 2.61 and dielectric loss of 0.0011 to 0.0014 at 10 GHz, along with enhanced mechanical strength and dimensional stability.
Smart Images

Figure BDA0004985408440000011 
Figure BDA0004985408440000026 
Figure BDA0004985408440000051
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electronic resin synthesis, and specifically relates to a halogen-free flame-retardant modified hydrocarbon resin and a preparation method thereof, a resin composition for a copper-clad laminate and an application thereof. Background Art
[0002] With the rapid development of artificial intelligence large-scale integrated circuits (AIGC), machine learning, 5G communications, millimeter-wave radar, the Internet of Things and other industries, the frequency of signal transmission on printed circuit boards is getting higher and higher, and high-frequency and high-speed copper-clad laminates have become a research hotspot in the current printed circuit board industry. In order to reduce the transmission loss in the high-frequency band and cope with the high-temperature soldering and high-layer assembly requirements during the substrate installation process, the insulating materials used for copper-clad laminates need to have halogen-free flame retardancy, better dielectric properties, heat resistance, glass transition temperature and dimensional stability.
[0003] In recent years, hydrocarbon resins such as polybutadiene resin, styrene-butadiene copolymer, ethylene propylene diene copolymer, cycloolefin copolymer, etc. have attracted much attention due to their small molecular chain polarity (the electronegativity of carbon atoms and hydrogen atoms is 2.5 and 2.1 respectively) and excellent dielectric properties (dielectric constant 2.4-2.8 at 1MHz, tanδ 0.0002-0.0006). However, these hydrocarbon resins have poor flame retardancy, extremely high chain segment flexibility, poor adhesion to the substrate, and the copper clad laminates made from them have insufficient flame retardancy. At the same time, they have disadvantages such as poor heat resistance, low glass transition temperature, insufficient rigidity, and large thermal expansion coefficient. Summary of the invention
[0004] The present application aims to overcome the deficiencies in the prior art and provide a halogen-free flame-retardant modified hydrocarbon resin and a preparation method thereof, a resin composition for copper-clad laminates and applications thereof. The halogen-free flame-retardant modified hydrocarbon resin provided by the present invention contains silicon elements, can provide halogen-free flame-retardant properties, and has excellent heat resistance, dimensional stability, dielectric properties, etc., and can be used in the field of high-frequency and high-speed printed circuit boards.
[0005] The present invention is achieved through the following technical solutions:
[0006] A halogen-free flame-retardant modified hydrocarbon resin comprises a hydrocarbon resin main chain, an organic silicon side chain and a benzocyclobutene group; the hydrocarbon resin main chain has a plurality of main chain double bonds and molecular side chain dangling double bonds; the benzocyclobutene group is grafted to at least one of the plurality of dangling double bonds; and the organic silicon side chain is grafted to at least one of the plurality of dangling double bonds.
[0007] The chemical structure of the halogen-free flame retardant modified hydrocarbon resin is shown in formula (I):
[0008]
[0009] Wherein, x is an integer from 1 to 100, and y and z are integers from 0 to 100;
[0010] R1, R2, R4, R7, R8, R9, R 10 Each is independently selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group containing 1 to 10 carbon atoms and ester group;
[0011] R3 is selected from a single bond, an alkyl group containing 2 to 10 carbon atoms, an aralkyl group containing 8 to 12 carbon atoms, an alkyl group containing 1 unsaturated bond and containing 2 to 10 carbon atoms, and an aralkyl group containing 1 unsaturated bond and containing 8 to 12 carbon atoms;
[0012] R5 is selected from Two or more of an alkyl group containing one unsaturated bond and having 2 to 10 carbon atoms and an aralkyl group containing one unsaturated bond and having 8 to 12 carbon atoms, at least Two structures, R 12 , R 13 , R 14 Each independently selected from phenyl, alkyl and ether groups having 1 to 10 carbon atoms, and aralkyl groups having 7 to 10 carbon atoms;
[0013] R6 is selected from hydrogen, phenyl, One or more of an alkyl group containing 1 to 10 carbon atoms, an aralkyl group containing 7 to 12 carbon atoms, an ether group and an ester group containing 1 to 10 carbon atoms, and a -R3-R5 connecting structure;
[0014] R 11 Selected from hydrogen, Phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group and ester group containing 1 to 10 carbon atoms, one or more of which R 12 , R 13 , R 14 Each is independently selected from a phenyl group, an alkyl group having 1 to 10 carbon atoms, an ether group, and an aralkyl group having 7 to 10 carbon atoms.
[0015] As some possible implementation methods of the present application, the main chain of the hydrocarbon resin comes from a hydrocarbon resin, and the general chemical structure of the hydrocarbon resin is shown in Formula II:
[0016]
[0017] Wherein, k is an integer from 1 to 100, and j and n are integers from 0 to 100;
[0018] R 15 , R16 , R 18 , R 19 , R 21 , R 22 , R 23 , R 24 Each is independently selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group containing 1 to 10 carbon atoms and ester group;
[0019] R 17 An alkyl group containing one unsaturated bond and having 2 to 10 carbon atoms or an aralkyl group containing one unsaturated bond and having 8 to 12 carbon atoms;
[0020] R 20 One or more selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group and ester group containing 1 to 10 carbon atoms, alkyl containing 1 unsaturated bond and 2 to 10 carbon atoms, and aralkyl containing 1 unsaturated bond and 8 to 12 carbon atoms.
[0021] To achieve the above-mentioned purpose, the present application also provides a method for preparing a halogen-free flame retardant modified hydrocarbon resin, wherein the hydrocarbon resin is first subjected to a hydrosilylation reaction with silicone, and then the addition product is subjected to a Heck reaction with a halogenated benzocyclobutene. The obtained benzocyclobutene silicon-modified hydrocarbon resin is subjected to a hydrogenation reaction to obtain the halogen-free flame retardant modified hydrocarbon resin.
[0022] As some possible implementation methods of the present application, the preparation method of the halogen-free flame retardant modified hydrocarbon resin specifically includes the following steps:
[0023] a. Preparation of silicone-modified hydrocarbon resin
[0024] According to the mass ratio of 1:0.1~0.5:1.6×10 -4 ~5×10 -3 Add hydrocarbon resin, dehydrated toluene and chloroplatinic acid to a clean reaction bottle in sequence, heat to 70-90°C under stirring, dropwise add silicone with a double bond molar amount of 0.01-0.3 times that of the hydrocarbon resin within 1-2 hours, and keep warm for reaction for 8-20 hours; after the reaction, add an appropriate amount of dehydrated toluene to dilute the solid content of the material to 25-35%, and obtain a colorless solution after silica gel adsorption and filtration;
[0025] b. Benzocyclobutene of organosilicon-modified hydrocarbon resin;
[0026] Under anhydrous and inert gas conditions, take an appropriate amount of the colorless solution in step a into a reaction bottle, add measured halogenated benzocyclobutene, acid binding agent, and catalyst A, and maintain the reaction temperature at 60-100° C. to react the organosilicon-modified hydrocarbon resin with the halogenated benzocyclobutene; monitor the degree of reaction by chromatography during the reaction to determine the reaction endpoint; when the reaction is completed, that is, when the reaction reaches the endpoint, wash the reaction material with water to neutrality, heat up for dehydration, remove impurities by silica gel adsorption, filter, and perform reduced pressure distillation operations to obtain a benzocyclobutene silicon-modified hydrocarbon resin;
[0027] c. Catalytic hydrogenation of hydrocarbon resin modified by silicon benzocyclobutene;
[0028] The benzocyclobutene silicon modified hydrocarbon resin in step c is dissolved in a proper amount of solvent, and a catalyst B with a mass fraction of 0.01% to 0.8% of the benzocyclobutene silicon modified hydrocarbon resin is added, stirred evenly, and a proper amount of hydrogen is introduced, and a hydrogenation reaction is carried out at 20 to 100° C. and a reaction pressure of 0.1 to 7 MPa for 1 to 10 hours. After the reaction is completed, the halogen-free flame retardant modified hydrocarbon resin is obtained by filtering or washing with pure water and distilling the solvent under reduced pressure.
[0029] As some possible implementation methods of the present application, the molar ratio of the double bonds of the halogenated benzocyclobutene to the organosilicon-modified hydrocarbon resin is 0.01 to 1:1; and the molar ratio of the acid-binding agent to the halogenated benzocyclobutene is 1 to 1.5:1.
[0030] As some possible implementation methods of the present application, the catalyst A is a mixture of a metal compound and a ligand, the metal compound includes but is not limited to palladium chloride, rhodium chloride, palladium acetate, bistriphenylphosphine palladium dichloride, platinum chloride, platinic acid, methacrylate palladium, bis(tributylphosphine)platinum chloride, and the ligand includes but is not limited to triphenylphosphine and tri(o-methylphenyl)phosphine; the molar ratio of the metal compound to the ligand is 1:2.4-6.0, and the molar ratio of the metal compound to the halogenated benzocyclobutene is 2×10 -3 ~7×10 -3 :1;
[0031] As some possible implementation methods of the present application, the catalyst B can be a heterogeneous catalyst or a homogeneous catalyst. The heterogeneous catalyst includes but is not limited to nickel catalysts and transition metal catalysts supported on carriers such as activated carbon, diatomaceous earth, and alumina; the homogeneous catalyst includes but is not limited to aluminum / nickel catalytic systems, metallocene catalysts, platinum metal catalysts, rhodium metal catalysts, and palladium metal catalysts.
[0032] As some possible implementation methods of the present application, the solvent is a non-polar solvent, including but not limited to toluene, xylene, cyclohexane, and n-hexane.
[0033] As some possible embodiments of the present application, the halogenated benzocyclobutene is selected from 4-bromobenzocyclobutene, 4-chlorobenzocyclobutene, and 4-iodobenzocyclobutene.
[0034] As some possible implementation modes of the present application, the acid binding agent includes but is not limited to pyridine, triethylamine, trimethylamine, sodium bicarbonate, potassium bicarbonate, sodium carbonate, and potassium carbonate.
[0035] In addition, to achieve the above-mentioned purpose, the present application also provides a resin composition for copper clad laminates, comprising the following components in parts by weight:
[0036] 65-79 parts of halogen-free flame-retardant modified hydrocarbon resin, 21-35 parts by weight of low molecular weight phosphorus-containing unsaturated resin, 0.01% to 0.22% by weight of initiator of the total weight of the resin, 25% to 53% by weight of filler of the total weight of the resin, and 34% to 36% by weight of solvent of the total weight of the resin composition;
[0037] The total mass of the resin refers to the total mass of the halogen-free flame retardant modified hydrocarbon resin and the low molecular weight phosphorus-containing unsaturated resin.
[0038] In this scheme, the resin composition for copper clad laminates includes a halogen-free flame-retardant modified hydrocarbon resin, and an organic silicon structure is introduced into the hydrocarbon resin to exert a flame retardant effect in the condensed phase, thereby improving the flame retardant properties of the hydrocarbon resin, while maintaining most of the structural characteristics of the hydrocarbon resin and having good solubility in organic solvents;
[0039] The halogen-free flame-retardant modified hydrocarbon resin provided in the present application cannot meet the requirements of halogen-free flame retardancy in the field of copper-clad laminates only through silicon flame retardancy. The resin composition for copper-clad laminates provided in the present application also includes a low molecular weight phosphorus-containing unsaturated resin, which can achieve phosphorus-silicon synergistic flame retardancy with the halogen-free flame-retardant modified hydrocarbon resin, thereby making the copper-clad laminate reach UL94 V0 level;
[0040] In the resin composition for copper-clad laminates provided in the present application, a low molecular weight phosphorus-containing unsaturated resin is used as a reactive flame retardant, and copolymerizes with a halogen-free flame-retardant modified hydrocarbon resin to form a cross-linked network structure, thereby giving the resin composition excellent heat resistance;
[0041] The resin composition for copper-clad laminate provided by the invention further comprises an initiator, a filler and a solvent.
[0042] As some possible embodiments of the present application, the phosphorus-containing unsaturated resin is a phosphorus-containing compound with two terminal double bonds, and the phosphorus-containing compound contains a DOPO structure (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) or a DPO structure (diphenylphosphine oxide).
[0043] As some possible embodiments of the present application, the phosphorus-containing unsaturated resin is a compound formed by esterification or etherification reaction of DOPO-HQ (10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide), DPO-HQ (2,5-dihydroxyphenyl diphenyl phosphine oxide), DOPO-NQ [2-(6-oxidized-6H-diphenyl (c, e) (1,2) oxaphosphorinane-6-yl)-1,4-naphthalene diol], DPO-NQ (1,4-dihydroxynaphthyl diphenyl phosphine oxide), bis-DOPO-HQ, bis-DOPO-NQ, bis-DPO-NQ, bis-DPO-HQ and unsaturated monomers; the unsaturated monomers include but are not limited to allyl chloride, acrylic acid, methacrylic acid, methacryloyl chloride, p-vinyl benzoic acid, and p-vinyl benzyl chloride.
[0044] As some possible implementation methods of the present application, the chemical structural formula of the phosphorus-containing unsaturated resin includes but is not limited to the following structure:
[0045]
[0046]
[0047] As some possible implementation methods of the present application, the initiator is any one of dicumyl peroxide (DCP for short), di-tert-butyl peroxide (DTBP for short), and tert-butyl perbenzoate (CP-01 for short);
[0048] As some possible implementation methods of the present application, the filler is any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, and kaolin;
[0049] As some possible implementation methods of the present application, the solvent is any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, and propylene glycol methyl ether acetate.
[0050] In addition, to achieve the above-mentioned purpose, the present application also provides an application of a resin composition for copper clad laminates in the preparation of halogen-free flame-retardant copper clad laminates.
[0051] Wherein, the preparation method of the halogen-free flame-retardant copper clad laminate is as follows:
[0052] S1. The resin composition for copper clad laminate is uniformly mixed to form a resin glue, glass fibers are arranged in the resin glue, immersed and then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130° C. to 170° C. for 4 to 7 minutes to obtain a halogen-free flame retardant semi-cured sheet;
[0053] S2 overlaps several layers of semi-cured sheets and attaches copper foil on both sides, places them in a hot press at a temperature of 150-170°C, and gradually increases the pressure to 0.2-4MPa depending on the glue flow situation, presses for 0.5-1h, then gradually heats up to 195-210°C and hot presses for 4-8h, then naturally cools and releases the pressure to obtain a halogen-free flame-retardant copper clad laminate.
[0054] As some possible implementation modes of the present application, the glass fiber cloth model is selected from 1080E, 2116, 2313, 3313, and 7628.
[0055] There is no limitation on the number of laminated layers of the semi-cured sheets, which can be selected from any number within the process achievable range.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] (1) The present invention introduces an organic silicon structure into hydrocarbon resin through a hydrosilane addition reaction, and improves the flame retardant properties of hydrocarbon resin through a condensed phase flame retardant effect. Compared with directly introducing phosphorus into hydrocarbon resin, such as the addition reaction of DOPO with a carbon-hydrogen double bond, the silicon-modified hydrocarbon resin of the present invention has less influence on the structural properties of the hydrocarbon resin, maintains good solubility in organic solvents, and the organic silicon used in the present invention is easier to remove the unreacted modifier, thereby achieving the purpose of purification.
[0058] (2) After the organic silicon structure is introduced into the hydrocarbon resin, the Si-C bond has high thermal stability, which can improve the heat resistance of the hydrocarbon resin; the Si-C bond has low polarity, which can enable the hydrocarbon resin to maintain excellent dielectric properties;
[0059] (3) The halogen-free flame-retardant modified hydrocarbon resin of the present invention contains benzocyclobutene groups, which can enhance the rigidity of the main chain of the molecule, increase the crosslinking density of the hydrocarbon resin cured product, and further improve the heat resistance, mechanical strength and dimensional stability of the hydrocarbon resin cured product.
[0060] (4) The present invention treats the hydrocarbon resin by hydrogenation, so that the hydrocarbon resin can maintain low and stable dielectric properties; compared with benzocyclobutene hydrocarbon resin, it combines the performance characteristics of benzocyclobutene groups and silicone, and has halogen-free flame retardant properties and better heat resistance and dielectric properties;
[0061] (5) The resin composition for copper clad laminates provided by the present invention is used, and a halogen-free flame retardant modified hydrocarbon resin and a low molecular weight phosphorus-containing unsaturated resin (a reactive flame retardant) are compounded. Phosphorus is introduced into the resin composition system through copolymerization to exert the synergistic effect of phosphorus and silicon, so that the flame retardant performance of the cured board of the resin composition for copper clad laminates reaches UL94 V0 level; the copper clad laminates prepared from the resin composition for copper clad laminates of the present invention have excellent comprehensive properties: a dielectric constant of 2.53 to 2.61 and a dielectric loss of 0.0011 to 0.0014 at 10 GHz; a glass transition temperature of 215 to 227°C and a peel strength of 1.21 to 1.35 N / mm, that is, it has excellent comprehensive properties.
[0062] (6) The preparation process of the present invention is easy to operate, and the prepared halogen-free flame-retardant modified hydrocarbon resin and resin composition for copper-clad laminate are suitable for the field of high-performance printed circuit boards and have strong practicality. DETAILED DESCRIPTION
[0063] The following is a clear and complete description of the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application.
[0064] Part I Preparation of Halogen-free Flame-retardant Modified Hydrocarbon Resin
[0065] Example 1-1:
[0066] In a clean reaction bottle, 100g hydrocarbon resin Ricon 157 (polybutadiene resin), 25g dehydrated toluene, and 0.1mmol chloroplatinic acid were added in sequence, and the temperature was raised to 80°C under stirring. 28.9g trimethylsilane was added dropwise within 1h, and the reaction was kept warm for 15h. After the reaction, an appropriate amount of dehydrated toluene was added to dilute the solid content of the material to 25%. A colorless solution was obtained after silica gel adsorption and filtration.
[0067] Under anhydrous and inert gas conditions, the colorless solution was taken into a reaction bottle, 142 g of 4-bromobenzocyclobutene, 59.5 g of trimethylamine, 0.23 g of palladium chloride, and 0.79 g of triphenylphosphine were added, and the temperature was raised to 78°C for reaction. The degree of reaction was monitored by chromatography during the reaction. When the reaction reached the end point, the reaction material was washed with water to neutrality, heated for dehydration, silica gel adsorption for impurity removal, filtration, and reduced pressure distillation of toluene to obtain 203 g of benzocyclobutene silicon-modified hydrocarbon resin.
[0068] The obtained benzocyclobutene silicon modified hydrocarbon resin was dissolved in a suitable solvent, 0.26 g of palladium carbon (Pd / C) catalyst was added, stirred evenly, a suitable amount of hydrogen was introduced, and hydrogenation reaction was carried out at 65° C. and a reaction pressure of 2 MPa for 3 h. After the reaction was completed, a light yellow halogen-free flame retardant modified hydrocarbon resin was obtained by filtering and distilling the solvent under reduced pressure. The resin number average molecular weight was 3471 as determined by gel permeation chromatography.
[0069] Embodiment 1-2:
[0070] In a clean reaction bottle, 100g hydrocarbon resin Ricon 181 (butadiene-styrene copolymer), 20g dehydrated toluene, and 2.8mmol chloroplatinic acid were added in sequence, and the temperature was raised to 85°C under stirring. 9.5g trimethylsilane was added dropwise within 1h, and the reaction was kept warm for 10h. After the reaction, an appropriate amount of dehydrated toluene was added to dilute the solid content of the material to 30%. A colorless solution was obtained after silica gel adsorption and filtration.
[0071] Under anhydrous and inert gas conditions, the colorless solution was taken into a reaction bottle, 87.6 g of 4-bromobenzocyclobutene, 38.2 g of potassium carbonate, 0.29 g of palladium chloride, and 0.94 g of triphenylphosphine were added, and the temperature was raised to 83° C. for reaction. The degree of reaction was monitored by chromatography during the reaction. When the reaction reached the end point, the reaction material was washed with water to neutrality, heated for dehydration, silica gel adsorption for impurity removal, filtered, and toluene was distilled under reduced pressure to obtain 155 g of benzocyclobutene silicon-modified hydrocarbon resin.
[0072] The obtained benzocyclobutene silicon modified hydrocarbon resin was dissolved in a suitable solvent, 0.19 g of palladium carbon (Pd / C) catalyst was added, stirred evenly, a suitable amount of hydrogen was introduced, and hydrogenation reaction was carried out at 65° C. and a reaction pressure of 2 MPa for 3 h. After the reaction was completed, a light yellow halogen-free flame retardant modified hydrocarbon resin was obtained by filtering and distilling the solvent under reduced pressure. The resin number average molecular weight was 4924 as determined by gel permeation chromatography.
[0073] Embodiment 1-3:
[0074] In a clean reaction bottle, 100g hydrocarbon resin Ricon 100 (butadiene-styrene copolymer), 40g dehydrated toluene, and 5.2mmol chloroplatinic acid were added in sequence, and the temperature was raised to 75°C under stirring. 21.8g trimethoxysilane was added dropwise within 1h, and the reaction was kept warm for 20h. After the reaction, an appropriate amount of dehydrated toluene was added to dilute the solid content of the material to 28%. A colorless solution was obtained after silica gel adsorption and filtration.
[0075] Under anhydrous and inert gas conditions, the colorless solution was added to a reaction bottle, 163.5 g of 4-bromobenzocyclobutene, 67.8 g of potassium carbonate, 0.41 g of palladium acetate, and 1.26 g of triphenylphosphine were added, and the temperature was raised to 75°C for reaction. During the reaction, the degree of reaction was monitored by chromatography to determine the end point of the reaction. When the reaction reached the end point, the reaction material was washed with water to neutrality, heated for dehydration, silica gel adsorption for impurity removal, filtered, and toluene was distilled under reduced pressure to obtain 209 g of benzocyclobutene silicon-modified hydrocarbon resin.
[0076] The obtained benzocyclobutene silicon modified hydrocarbon resin was dissolved in an appropriate amount of solvent, 0.48g of palladium carbon (Pd / C) catalyst was added, stirred evenly, and an appropriate amount of hydrogen was introduced. The hydrogenation reaction was carried out at 65°C and a reaction pressure of 2 MPa for 3 hours. After the reaction was completed, the halogen-free flame retardant modified hydrocarbon resin was obtained by filtering and decompression distillation of the solvent. A light yellow halogen-free flame retardant modified hydrocarbon resin was obtained, and the number average molecular weight of the resin was 9208 as determined by gel permeation chromatography.
[0077] Embodiment 1-4:
[0078] In a clean reaction bottle, 100g hydrocarbon resin Ricon 257 (butadiene-styrene-divinylbenzene copolymer), 40g dehydrated toluene, and 2.6mmol chloroplatinic acid were added in sequence, and the temperature was raised to 80°C under stirring. 23.8g trimethoxysilane was added dropwise within 1h, and the reaction was kept warm for 14h. After the reaction, an appropriate amount of dehydrated toluene was added to dilute the solid content of the material to 28%, and a colorless solution was obtained after silica gel adsorption and filtration.
[0079] Under anhydrous and inert gas conditions, the colorless solution was added to a reaction bottle, 161.3 g of 4-bromobenzocyclobutene, 73.6 g of potassium carbonate, 0.69 g of palladium acetate, and 2.59 g of triphenylphosphine were added, and the temperature was raised to 78°C for reaction. During the reaction, the degree of reaction was monitored by chromatography to determine the end point of the reaction. When the reaction reached the end point, the reaction material was washed with water to neutrality, heated for dehydration, silica gel adsorption for impurity removal, filtered, and toluene was distilled under reduced pressure to obtain 209 g of benzocyclobutene silicon-modified hydrocarbon resin.
[0080] The obtained benzocyclobutene silicon modified hydrocarbon resin was dissolved in a suitable solvent, 0.48 g of palladium carbon (Pd / C) catalyst was added, stirred evenly, a suitable amount of hydrogen was introduced, and hydrogenation reaction was carried out at 65° C. and a reaction pressure of 2 MPa for 3 hours. After the reaction was completed, a light yellow halogen-free flame retardant modified hydrocarbon resin was obtained by filtering and distilling the solvent under reduced pressure. The resin number average molecular weight was 11176 as determined by gel permeation chromatography.
[0081] Embodiment 1-5:
[0082] In a clean reaction bottle, add 100g hydrocarbon resin B1000 (polybutadiene resin), 43g dehydrated toluene, and 8.8mmol chloroplatinic acid in sequence, heat to 90°C under stirring, add 10.1g triethylsilane dropwise within 1h, and keep warm for 9h; after the reaction, add appropriate amount of dehydrated toluene to dilute the solid content of the material to 28%, and a colorless solution can be obtained after silica gel adsorption and filtration;
[0083] Under anhydrous and inert gas conditions, the colorless solution was added to a reaction bottle, 288.1 g 4-bromobenzocyclobutene, 118.4 g potassium carbonate, 1.06 g palladium acetate, and 4.96 g triphenylphosphine were added, and the temperature was raised to 85°C for reaction. During the reaction, the degree of reaction was monitored by chromatography to determine the end point of the reaction. When the reaction reached the end point, the reaction material was washed with water to neutrality, heated for dehydration, silica gel adsorption for impurity removal, filtered, and toluene was distilled under reduced pressure to obtain 258 g benzocyclobutene silicon-modified hydrocarbon resin.
[0084] The obtained benzocyclobutene silicon modified hydrocarbon resin was dissolved in a proper amount of solvent, 1.29 g of palladium carbon (Pd / C) catalyst was added, stirred evenly, a proper amount of hydrogen was introduced, and hydrogenation reaction was carried out at 65° C. and a reaction pressure of 2 MPa for 2 h. After the reaction was completed, a light yellow halogen-free flame retardant modified hydrocarbon resin was obtained by filtering and distilling the solvent under reduced pressure. The resin number average molecular weight was 3120 as determined by gel permeation chromatography.
[0085] Part 2 Preparation of Halogen-free Flame-retardant Resin Copper Clad Laminate (Examples 2-1 to 2-5)
[0086] The steps of preparing the resin composition for copper clad laminate and the high-frequency copper clad laminate are as follows:
[0087] 65-79 parts of halogen-free flame retardant modified hydrocarbon resin, 21-35 parts by mass of phosphorus-containing unsaturated resin, 0.01%-0.22% of the total mass of the resin (the total mass of the resin refers to the total mass of the halogen-free flame retardant modified hydrocarbon resin and the phosphorus-containing unsaturated resin, the same below) of an initiator, 25%-53% of the total mass of the resin filler and 34%-36% of the total mass of the resin composition The solvent is uniformly mixed to prepare a resin glue, glass fibers are arranged in the resin glue and immersed, then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130°C to 170°C for 4 to 7 minutes to prepare a halogen-free flame retardant semi-cured sheet;
[0088] Subsequently, several layers of semi-cured sheets are stacked, and copper foil is attached on both sides. They are placed in a hot press at a temperature of 150-170°C. Depending on the glue flow, the pressure is gradually increased to 0.2-4MPa, pressed for 0.5-1h, and then gradually heated to 195-210°C and hot pressed for 4-8h. After natural cooling and pressure relief, the halogen-free flame-retardant copper clad laminate is obtained.
[0089] Among them, the components and specific amounts of the high-speed copper clad laminates of Examples 2-1 to 2-5 are shown in Table 1:
[0090] Table 1: Components and dosage of high-speed copper-clad laminates of Examples 2-1 to 2-5:
[0091]
[0092]
[0093] The raw materials used in the examples in Table 1 are:
[0094] The halogen-free flame-retardant modified hydrocarbon resin used in Example 2-1 is from Example 1-1;
[0095] The halogen-free flame-retardant modified hydrocarbon resin used in Example 2-2 is from Example 1-2;
[0096] The halogen-free flame-retardant modified hydrocarbon resin used in Examples 2-3 is from Examples 1-3;
[0097] The halogen-free flame-retardant modified hydrocarbon resin used in Examples 2-4 is from Examples 1-4;
[0098] The halogen-free flame-retardant modified hydrocarbon resin used in Examples 2-5 is from Examples 1-5;
[0099] The phosphorus-containing unsaturated resin used in Examples 2-1, 2-2, and 2-4 has the following structure:
[0100]
[0101] The phosphorus-containing unsaturated resin used in Examples 2-3 and 2-5 has the following structure:
[0102]
[0103] The initiator used in Examples 2-1 to 2-5 was dicumyl peroxide (DCP for short), produced by Hongbaoli Group Co., Ltd.;
[0104] The filler used in Examples 2-1 to 2-5 is silicon dioxide, Jiangsu Lianrui DQ1040;
[0105] The solvent used in Examples 2-1 to 2-5 was butanone.
[0106] Comparative Example 1:
[0107] 100 parts by mass of polybutadiene resin (Ricon 134), 0.2 parts by mass of dicumyl peroxide and (appropriate amount) of solvent were uniformly stirred and mixed to prepare an epoxy resin composition resin glue for copper clad laminates with a solid content of 64% to 66%. Glass fibers were arranged in the resin glue and immersed and then taken out, and then hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130° C. to 170° C. for baking for 4 to 7 minutes to obtain a prepreg. 10 layers of prepregs were stacked, and copper foils were attached on both sides, and placed in a hot press at a temperature of 150 to 170° C., and gradually pressurized to 0.2 to 4 MPa (depending on the glue flow), pressed for 0.5 to 1 h, and then gradually heated to 195 to 210° C. for hot pressing for 4 to 8 h, and then naturally cooled and depressurized to obtain a copper clad laminate of Comparative Example 1.
[0108] Comparative Example 2:
[0109] 75 parts by mass of benzocyclobutene hydrocarbon resin (hydrocarbon resin B1000 was benzocyclobutene-treated according to the conditions of Example 1-5), 25 parts by mass of phosphorus-containing unsaturated resin 0.19 mass parts of dicumyl peroxide and (appropriate amount) of solvent are uniformly stirred and mixed to prepare a resin glue solution of epoxy resin composition for copper clad laminate with a solid content of 64% to 66%, glass fiber is arranged in the resin glue solution and immersed and then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130°C to 170°C for baking for 4 to 7min to obtain a prepreg; 12 layers of prepregs are stacked, and copper foils are attached on both sides, and placed in a hot press at a temperature of 150 to 170°C, and gradually pressurized to 0.2 to 4MPa (depending on the glue flow), pressed for 0.5 to 1h, and then gradually heated to 195 to 210°C for hot pressing for 4 to 8h, and then naturally cooled and depressurized to obtain a copper clad laminate of Comparative Example 2.
[0110] Comparative Example 3:
[0111] Benzocyclobutene hydrocarbon resin (hydrocarbon resin B1000) was treated according to the conditions of Examples 1-5. Benzocyclobutene and Hydroprocessing ) 75 parts by mass, 25 parts by mass of phosphorus-containing unsaturated resin 0.19 mass parts of diisopropylbenzene peroxide and (appropriate amount) of solvent are uniformly stirred and mixed to prepare a resin glue solution of epoxy resin composition for copper clad laminate with a solid content of 64% to 66%, glass fiber is arranged in the resin glue solution and immersed and then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130°C to 170°C for baking for 4 to 7min to obtain a prepreg; 12 layers of prepregs are stacked, and copper foils are attached on both sides, and placed in a hot press at a temperature of 150 to 170°C, and gradually pressurized to 0.2 to 4MPa (depending on the glue flow), pressed for 0.5 to 1h, and then gradually heated to 195 to 210°C for hot pressing for 4 to 8h, and then naturally cooled and depressurized to obtain a copper clad laminate of Comparative Example 3.
[0112] The performance parameters of the copper clad laminates prepared in Examples 2-1 to 2-5 and the copper clad laminates prepared in Comparative Examples 1 to 3 are compared, as shown in Table 2:
[0113] Table 2
[0114]
[0115] Note: Df / 10GHz(24h) and Df / 10GHz(90days) refer to the test indicators within 24 hours and 90 days after sample preparation.
[0116] As can be seen from Table 2, the composition for copper clad laminate provided in the present application comprises a halogen-free flame retardant modified hydrocarbon resin and a phosphorus-containing unsaturated resin, and the halogen-free flame retardant copper clad laminate prepared therefrom can reach the V0 level in the UL94 test. Compared with the comparative example, it is found that comparative example 1 uses unmodified hydrocarbon resin to prepare copper clad laminates, and the resulting copper clad laminates have poor heat resistance and mechanical properties, and are not flame retardant; comparative example 2 benzocyclobutenes the hydrocarbon resin on the basis of comparative example 1, and matches the phosphorus-containing unsaturated resin, so that the heat resistance, mechanical properties, and flame retardant properties of the copper clad laminate obtained are improved, but the flame retardant properties cannot reach the V0 level of flame retardancy, and comparative example 3 hydrogenates the modified hydrocarbon resin on the basis of comparative example 2, and the dielectric properties stability of the resulting copper clad laminate is improved, and the halogen-free flame retardant of the embodiment cannot be achieved.
[0117] The relevant standards used in the technical indicators in this article are as follows:
[0118] Glass transition temperature Tg: measured by dynamic mechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;
[0119] Dielectric constant Dk and dielectric loss Df: Use SPDR method to test 10GHz data according to the method specified in IEC 61189-2-721;
[0120] CTE (Z-axis expansion coefficient): Tested according to the method specified in 2.4.24.5 of IPC-TM-650;
[0121] Peel strength: Test the peel strength of the metal cover layer according to the experimental conditions of "thermal stress" in the method specified in 2.4.8 of IPC-TM-650;
[0122] UL 94 flame retardant performance test: measured according to UL94 vertical burning test method.
[0123] In the above embodiments and comparative examples, the definition of "solid content" is: the percentage of the mass of non-volatile matter in the total mass of 100g sample (i.e., epoxy resin composition resin glue for copper clad laminate) after baking for 3 hours in an oven at 125°C, and the solid amount finally determined by adding the mass of water solvent is calculated based on the mass of the non-volatile matter.
[0124] In the above embodiments: the percentages used, unless otherwise specified, are all mass (weight) percentages or percentages known to those skilled in the art; the proportions used, unless otherwise specified, are all mass (weight) proportions; and the weights may be in grams or kilograms.
[0125] In the above embodiments, the process parameters (temperature, time, concentration, pressure, etc.) in each step and the numerical values of the amounts of each component are ranges, and any point can be applied.
[0126] The technical contents not specifically described in the present invention and the above embodiments are the same as the prior art, and the raw materials are all commercially available products.
[0127] The present invention is not limited to the above embodiments, and all of the contents of the present invention can be implemented and have the above good effects.
Claims
1. A halogen-free flame retardant modified hydrocarbon resin, characterized in that: It comprises a hydrocarbon resin main chain, an organic silicon side chain and a benzocyclobutene group; the hydrocarbon resin main chain has a plurality of main chain double bonds and molecular side chain dangling double bonds; the benzocyclobutene group is grafted to at least one of the plurality of dangling double bonds; and the organic silicon side chain is grafted to at least one of the plurality of dangling double bonds.
2. The halogen-free flame-retardant modified hydrocarbon resin according to claim 1, characterized in that: The chemical structure of the halogen-free flame retardant modified hydrocarbon resin is shown in formula (I): Wherein, x is an integer from 1 to 100, and y and z are integers from 0 to 100; R1, R2, R4, R7, R8, R9, R 10 Each is independently selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group containing 1 to 10 carbon atoms and ester group; R3 is selected from a single bond, an alkyl group containing 2 to 10 carbon atoms, an aralkyl group containing 8 to 12 carbon atoms, an alkyl group containing 1 unsaturated bond and containing 2 to 10 carbon atoms, and an aralkyl group containing 1 unsaturated bond and containing 8 to 12 carbon atoms; R5 is selected from Two or more of an alkyl group containing one unsaturated bond and having 2 to 10 carbon atoms and an aralkyl group containing one unsaturated bond and having 8 to 12 carbon atoms, at least Two structures, R 12 , R 13 , R 14 Each independently selected from phenyl, alkyl and ether groups having 1 to 10 carbon atoms, and aralkyl groups having 7 to 10 carbon atoms; R6 is selected from hydrogen, phenyl, One or more of an alkyl group containing 1 to 10 carbon atoms, an aralkyl group containing 7 to 12 carbon atoms, an ether group and an ester group containing 1 to 10 carbon atoms, and a -R3-R5 connecting structure; R 11 Selected from hydrogen, Phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group and ester group containing 1 to 10 carbon atoms, one or more of which R 12 , R 13 , R 14 Each is independently selected from a phenyl group, an alkyl group having 1 to 10 carbon atoms, an ether group, and an aralkyl group having 7 to 10 carbon atoms.
3. The halogen-free flame-retardant modified hydrocarbon resin according to claim 1, characterized in that: The main chain of the hydrocarbon resin comes from hydrocarbon resin, and the general chemical structure of the hydrocarbon resin is shown in Formula II: Wherein, k is an integer from 1 to 100, and j and n are integers from 0 to 100; R 15 , R 16 , R 18 , R 19 , R 21 , R 22 , R 23 , R 24 Each is independently selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group containing 1 to 10 carbon atoms and ester group; R 17 An alkyl group containing one unsaturated bond and having 2 to 10 carbon atoms or an aralkyl group containing one unsaturated bond and having 8 to 12 carbon atoms; R 20 One or more selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group and ester group containing 1 to 10 carbon atoms, alkyl containing 1 unsaturated bond and 2 to 10 carbon atoms, and aralkyl containing 1 unsaturated bond and 8 to 12 carbon atoms.
4. The method for preparing a halogen-free flame retardant modified hydrocarbon resin according to any one of claims 1 to 3, characterized in that: Firstly, the hydrocarbon resin and the organosilicon undergo a hydrosilylation reaction, and then the addition product undergoes a Heck reaction with a halogenated benzocyclobutene. The obtained benzocyclobutene silicon-modified hydrocarbon resin undergoes a hydrogenation reaction to obtain the halogen-free flame-retardant modified hydrocarbon resin.
5. The method for preparing a halogen-free flame-retardant modified hydrocarbon resin according to claim 4, characterized in that: The specific steps include: a. Preparation of silicone-modified hydrocarbon resin According to the mass ratio of 1:0.1~0.5:1.6×10 -4 ~5×10 -3 Add hydrocarbon resin, dehydrated toluene and chloroplatinic acid to a clean reaction bottle in sequence, heat to 70-90°C under stirring, dropwise add silicone with a double bond molar amount of 0.01-0.3 times that of the hydrocarbon resin within 1-2 hours, and keep warm for reaction for 8-20 hours; after the reaction, add an appropriate amount of dehydrated toluene to dilute the solid content of the material to 25-35%, and obtain a colorless solution after silica gel adsorption and filtration; b. Benzocyclobutene of organosilicon-modified hydrocarbon resin; Under anhydrous and inert gas conditions, take an appropriate amount of the colorless solution in step a into a reaction bottle, add measured halogenated benzocyclobutene, acid binding agent, and catalyst A, and maintain the reaction temperature at 60-100° C. to react the organosilicon-modified hydrocarbon resin with the halogenated benzocyclobutene; after the reaction is completed, wash the reaction materials with water until neutral, heat up for dehydration, remove impurities by silica gel adsorption, filter, and perform reduced pressure distillation to obtain a benzocyclobutene silicon-modified hydrocarbon resin; c. Catalytic hydrogenation of hydrocarbon resin modified by silicon benzocyclobutene; The benzocyclobutene silicon modified hydrocarbon resin in step c is dissolved in a proper amount of solvent, and a catalyst B with a mass fraction of 0.01% to 0.8% of the benzocyclobutene silicon modified hydrocarbon resin is added, stirred evenly, and a proper amount of hydrogen is introduced, and a hydrogenation reaction is carried out at 20 to 100° C. and a reaction pressure of 0.1 to 7 MPa for 1 to 10 hours. After the reaction is completed, the halogen-free flame retardant modified hydrocarbon resin is obtained by filtering or washing with pure water and distilling the solvent under reduced pressure.
6. The method for preparing a halogen-free flame-retardant modified hydrocarbon resin according to claim 5, characterized in that: The molar ratio of the double bonds of the halogenated benzocyclobutene to the organosilicon-modified hydrocarbon resin is 0.01-1:1; the molar ratio of the acid-binding agent to the halogenated benzocyclobutene is 1-1.5:
1.
7. The method for preparing a halogen-free flame-retardant modified hydrocarbon resin according to claim 5, characterized in that: The catalyst A is a mixture of a metal compound and a ligand, the molar ratio of the metal compound to the ligand is 1:2.4-6.0, and the molar ratio of the metal compound to the halogenated benzocyclobutene is 2×10 -3 ~7×10 -3 :
1.
8. A resin composition for copper-clad laminates, characterized in that: It includes the following components by weight: 65-79 parts of the halogen-free flame-retardant modified hydrocarbon resin according to any one of claims 1 to 3, 21-35 parts by weight of a phosphorus-containing unsaturated resin, 0.01% to 0.22% by weight of an initiator according to the total weight of the resin, 25% to 53% by weight of a filler according to the total weight of the resin, and 34% to 36% by weight of a solvent according to the total weight of the resin composition; The total mass of resin refers to the total mass of the halogen-free flame retardant modified hydrocarbon resin and the phosphorus-containing unsaturated resin.
9. A resin composition for copper-clad laminates according to claim 8, characterized in that: The phosphorus-containing unsaturated resin is a phosphorus-containing compound with two terminal double bonds, and the phosphorus-containing compound contains a DOPO structure or a DPO structure.
10. Use of the resin composition for copper clad laminates according to claim 8 or 9 in preparing halogen-free flame-retardant copper clad laminates.
Citation Information
Cited By
Acenaphthene alkenyl fluorine-containing hydrocarbon resin for M9-grade copper-clad plate and preparation method thereof
CN121949685A
